Continuity of Offending in Young Adulthood: A Test of Moffitt’s Snares Hypothesis - Widdowson, Alex O. (Crime & delinquency, 2024)
Moffitt?s snares hypothesis posits that snares?such as addiction to drugs and alcohol, time spent incarcerated, unemployment, teenage parenthood, high school dropout, and disabling injuries?can trap individuals into persistent patterns of offending during periods in the lifecourse when desistance is normative. We test this hypothesis using data from the National Longitudinal Survey of Youth 1997 to examine the associations and mechanisms between snare exposure and criminal offending during young adulthood. Results indicate that snare exposure was associated with increased offending and that this was in part due to snare exposure undermining a successful transition to adulthood, harming health, and producing social disadvantage. Moreover, the association between snare exposure and offending varied for different life-course offending trajectories.